Association Between HTLV-1 Genotypes and Risk of HAM/TSP - Saito, Mineki (Frontiers in Microbiology, 2019)
Human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a neurological disorder presenting with spastic paraparesis, sphincter dysfunction, and mild sensory disturbance in the lower extremities, which develops in a small minority of HTLV-1-infected individuals. HTLV-1-specific T cells are efficiently activated through dedicated human leukocyte antigen-mediated mechanisms, a process considered deeply involved with its pathogenesis. It has been reported that the lifetime risk of developing HAM/TSP differs between ethnic groups, and there is an association between HTLV-1 tax gene subgroups (i.e., tax subgroup-A or -B), which correspond to HTLV-1 “cosmopolitan subtype 1a subgroup A (i.e., transcontinental subgroup)” and “cosmopolitan subtype 1a subgroup B (i.e., Japanese subgroup)”, respectively, and the risk of HAM/TSP in the Japanese population. These findings suggest that a given host’s susceptibility to HAM/TSP is deeply connected with both differences in genetically determined components of the host immune response and HTLV-1 subgroup. Therefore, it is crucial for ongoing work to focus on developing novel treatments and preventative approaches for HAM/TSP. In this review, based on an overview of the topic and our latest research findings, the role of the HTLV-1 subgroup on the effects of virus–host interactions in the pathogenesis of HAM/TSP is discussed.